Investigating the shortcomings of the flow convergence method for quantification of mitral regurgitation in a pulsatile in-vitro environment and with computational fluid dynamics - Leister, Robin; Karl, Roger; Stroh, Lubov; Mereles, Derliz; Eden, Matthias; Neff, Luis; De Simone, Raffaele; Romano, Gabriele; Kriegseis, Jochen; Karck, Matthias; Lichtenstern, Christoph; Frey, Norbert; et al. (Cardiovascular engineering and technology, 2025)
The flow convergence method includes calculation of the proximal isovelocity surface area (PISA) and is widely used to classify mitral regurgitation (MR) with echocardiography. It constitutes a primary decision factor for determination of treatment and should therefore be a robust quantification method. However, it is known for its tendency to underestimate MR and its dependence on user expertise. The present work systematically compares different pulsatile flow profiles arising from different regurgitation orifices using transesophageal echocardiographic (TEE) probe and particle image velocimetry (PIV) as a reference in an in-vitro environment. It is found that the inter-observer variability using echocardiography is small compared to the systematic underestimation of the regurgitation volume for large orifice areas (up to 52%) where a violation of the flow convergence method assumptions occurs. From a flow perspective, a starting vortex was found as a dominant flow pattern in the regurgant jet for all orifice shapes and sizes. A series of simplified computational fluid dynamics (CFD) simulations indicate that selecting a suboptimal aliasing velocity during echocardiography measurements might be a primary source of potential underestimation in MR characterization via the PISA-based method, reaching up to 40%. In this study, it has been noted in clinical observations that physicians often select an aliasing velocity higher than necessary for optimal estimation in diagnostic procedures.